Low prevalence of hypertension with pharmacological treatments and associated factors - Gama, H (2013)
OBJECTIVE: To assess the determinants of the lack of pharmacological treatment for hypertension. METHODS: In 2005, 3,323 Mozambicans aged 25-64 years old were evaluated. Blood pressure, weight, height and smoking status were assessed following the Stepwise Approach to Chronic Disease Risk Factor Surveillance. Hypertensives (systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg and/or antihypertensive drug therapy) were evaluated for awareness of their condition, pharmacological and non-pharmacological management, as well as use of herbal or traditional remedies. Prevalence ratios (PR) were calculated, adjusted for sociodemographic characteristics, cardiovascular risk factors and non-pharmacological treatment. RESULTS: Most of the hypertensive subjects (92.3%), and nearly half of those aware of their condition were not treated pharmacologically. Among the aware, the prevalence of untreated hypertension was higher in men {PR = 1.61; 95% confidence interval (95%CI 1.10;2.36)} and was lower in subjects under non-pharmacological treatment (PR = 0.58; 95%CI 0.42;0.79); there was no significant association with traditional treatments (PR = 0.75; 95%CI 0.44;1.26). CONCLUSIONS: The lack of pharmacological treatment for hypertension was more frequent in men, and was not influenced by the presence of other cardiovascular risk factors; it could not be explained by the use of alternative treatments as herbal/traditional medicines or non-pharmacological management. It is important to understand the reasons behind the lack of management of diagnosed hypertension and to implement appropriate corrective actions to reduce the gap in the access to healthcare between developed and developing countries.